FALSE HADITH IN EDUCATION - Rima Melati; Dicky Yanda (Proceeding International Seminar of Islamic Studies, 2022)
False hadith means attributing (relying) a quote, deed, confession or character to the Prophet shallallaahu 'alaihi wa sallam. Even though it was not said, not done, not approval and not the nature of the Prophet. So, attributing something to the Prophet that is not from him is a false hadith. Like the hadith that says cleanliness is part of faith, this hadith is weak. Even so, but the essence of cleanliness is part of faith that can still be justified. Because Islam always emphasizes cleanliness and holiness, whether in a state of worship or not.Keywords: Hadith, Fake, Weak, Education